Role Of Organizational Development, Integrated Reporting Implementation and Optimizing on Regional Asset Management - Syaiful Hifni; Akhmad Sayudi; Rano Wijaya (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
Purpose: This study aims to describe how does the role of organizational development and integrated reporting<IR> implementation within optimizing on regional asset management. Design/methodology/approach: As qualitative research with subject of regional government in Indonesia. Used informational analysis approach from secondary data from archives related to regional asset management. Findings: The role of strategic, social, technical and administrative organizational development is relative more dominant in the clarity of the role of goals to be achieved in optimizing of regional asset management. Meanwhile, there are challenges either in meeting or to implement processes clarity to achieve an optimizing on regional assets management. The perspective of implementing <IR> for regional asset reporting is needed because of the role of the model in achieving organizational value, social and environmental accountability by reporting mechanism. Contribution: Result of research can be used as insight to implement the optimizing on regional asset management as well as in achievement sustainable regional asset management.